The Improvement of the Students’ Ability in Writing Procedure Text Using Video Recipe - Lating, Ahmad Zakqy Yamani (Universitas Pendidikan Mandalika, 2022)
Writing skill is one of the most difficult language skills to be mastered for foreign learners. Learners are demanded not only to master linguistic features but also to acquire non-linguistic aspects. To train learners, teachers should provide their learners with writing exercises as much as possible in classes. This study is aimed at investigating the effectiveness of video recipes to improve students’ writing procedure texts at the nineth-grade students of SMPN 1 Mojowarno, East Java. This study involved 32 students as participants that consisted of 16 males and 16 females. This study was designed in the classroom action research. The CAR procedure consisted of Planning, Implementing, observing, and reflecting. Each phase has activities dealing with the use of video recipe to improve students’ writing procedural texts. To state students’ criterion of success, the researcher enacted the score of 76. This study passed two cycles. In the first cycle, students still are achieving the passing grade. Students have achieved the passing in second cycle. Based on the results, the students showed their interest, pleasure, enthusiasm and curiosity during the implementation of video recipes. Therefore, this study can be inferred that video recipes was able to improve the students’ ability in writing procedure text at SMPN 1 Mojowarno.